CD44 and CD133 aptamer directed nanocarriers for cancer stem cells targeting. (19th January 2023) - Grover, Rakshita; Drall, Sahil; Poonia, Neelam; Kumar Jain, Gaurav; Aggarwal, Geeta; Lather, Viney; Kesharwani, Prashant; Pandita, Deepti; Goyal, Ramesh K.
Graphical abstract: Abstract: Cancer stem cells (CSCs) also known as tumour-initiating cells contribute not only to the onset and progression of tumor in most cancer types, but also play a definitive role in chemotherapy resistance and relapse due to its self-renewability. Various cell surface markers such as CD44 and CD133 are used in identification of aggressive CSCs. CD44 and CD133 are two most commonly expressed markers in various types of cancers including lung, pancreatic, ovarian, and prostate cancer. Targeting these markers with random short oligonucleotide sequences better known as aptamers conjugated nanocarriers is a better option to combat CSCs. The aptamer selection process can be efficiently achieved with Cell-SELEX technology which involves iterations of incubation with target biomolecule, selection, amplification and evaluation of random pool of oligonucleotide sequences. Aptamers could overcome the limitations of antibodies such as immunogenic responses, short shelf life and poor targeting. Various nanocarriers conjugated with antiCD44 and antiCD133 aptamers have been explored by scientific fraternity taking the merits of aptamers into consideration and have proved to be beneficial in targeting CSCs. This article reviews the recent advancements in aptamers and its conjugation with nanocarriers to obtain specific targeting of CSCs and higher efficacy than the current cancer therapy.